Media Baru, Ruang Publik Baru, dan Transformasi Komunikasi Politik di Indonesia - Salvatore Simarmata (Jurnal InterAct, 2014)
This article tries to unveil the transformative power of the new media platforms that reshape a new pattern of political communication in our democracy. Furthermore, the characteristics of new media have contributed significantly to the renaissance of an enabling public sphere. The structure of new media transforms the restricted and deep-rooted top-down pattern of political communication into one that is decentralized and bottom-up today. There are, at least, five forms of transformation in the pattern of political communication as the result of utilizing various features of the new media technology, namely e-government,  political campaign,  citizen’s aspirations channel, and decentralized political education. Some trends of the application in the context of general election’s micro-political communication (citizen-to-citizen) are discussed succinctly, such as Vote Cerdas BDG, Orang Baik, Bersih2014, Check Your Candidates, Mata Massa, Rumah Pemilu, and Jari Ungu.